Relações étnicas e “raciaIs” no contexto indígena: as práticas educativas na aldeia Ofaié-MS - VANESSA APARECIDA CAMPERLINGO SERRA (2022)
This study assumes as a general objective to investigate and analyze the pedagogical experiences in the educational context, as relationships between indigenous teachers of the Ofaié-E-Iniecheki school, located in Brasilândia, Mato Grosso do Sul. For a person both, as a background study to understand the role of interscholastic relationships through an online interview (Google Meet) with the teacher of the village Ofaié, Silvano de Moraes. In addition to the use of primary sources, such as the use of the 19th century Province Reports and separate documents, we looked into the social networks of some members of the Ofaié village, such as the teacher, the chief and the wife of the teacher who has a fundamental role in the relationship with the students. The centrality in the teacher is justified by taking him as a paradigm in the education of the Ofaié people of Brasilândia. Our central question was: how does the teacher deal with and organize school relationships with his students? Throughout the research, we worked with relevant references in the dialogue with the theoretical and methodological exercises of social relations, such as educational practices and other social relations. To conclude that it is necessary to observe and recognize that the Ofaié-E-Iniecheki of the peoples with rights to the preservation of their form and the politicians for the creation of form and the politicians can develop their cultural traditions so that they are part of the culture in culture permanent dialogue with the contexts that surround them.